Wound Care in Home Care: The Global Perspective - Peirce, Ben; Smart, Hiske; Carville, Keryln; Harris, Connie (HMP Communications, 2012)
Healthcare differs dramatically between countries. This chapter highlights the differences among home healthcare nurses who care for patients with wounds in South Africa, Australia, Canada, and the United States. The authors outline how home care is provided in each of these countries and describe the challenges and successes they have experienced. The authors’ insights provide valuable information for community-based providers around the world.Objectives: The reader will be challenged to: • Compare and contrast home care systems in different countries • Analyze the strengths and weaknesses of each system • Consider piloting ideas that may improve local wound home care services.